Die Legende vom Einhorn bei Michael Choniates: Quellen und Imitationen - TZIATZI-PAPAGIANNI, Maria (Byzantina Symmeikta, 2024)
This paper focuses on the poem of Michael Choniates on the image of the unicorn, which has not been systematically researched since its publication by Spyridon Lampros in 1880. I present a new critical edition of the poem based on the two manuscripts transmitting it, most notably the Vaticanus, which Lampros had not used for his edition. I argue that Choniates’ main source for the legend of the unicorn is the Byzantine novel Barlaam and Joasaph, by comparing Choniates’ verses with the text of his source. I proceed by tracing the iconographic models of this legend which inspired Choniates, primarily the representations of the unicorn in Greek psalteries. Finally, I examine its reception in the Byzantine literature after Choniates (especially in Manuel Philes) until the early 15th century, as well as in the iconographic tradition up to the 18th century.